VTO Model Tester with MindAR Library - Sanriomi Sintaro; Lucky Putra Dharmawan (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2023)
Augmented Reality is not a new technology, with more than 30 years of age, AR, which used to require large resources, can now even be run using a website application. The advantage of using a website is that the website application can be run on almost any device that supports a web browser. Web AR can also be used as a trial tool that can be used by customers to try on clothes or other products which is also known as VTO or Virtual Try On. The problem that arises from VTO Application is from the 3D designer side, which must make 3D Object and always readjust if the 3D is not suitable for VTO that requires accuracy of shape and size, that must be adjusted between 3D objects and human faces. The focus of this research is creating a website application that can connect to the internet so that 3D designers can easily access the VTO tester from any device to test 3D objects that have been created for Virtual Try On. The result of this research is that we can use local storage as a temporary storage medium and proof that local storage cannot also be used to store documents but also to store 3D objects. By immediately deleting temporary storage in local storage, the storage quota will not increase so that our local storage drives are not affected, the memory usage of only 10MB is also an advantage of this VTO Tester application, because it does not require a large memory to run the VTO Tester. In terms of memory usage, there is no memory leak that results when using VTO Tester application, this proves that the application developed can be used repeatedly without worrying about burdened computer performance.